A comparison of profilometer and AutoCAD software techniques in evaluation of implant angulation in vitro - Assunção, Wirley Gonçalves [UNESP]; Gomes, Érica Alves [UNESP]; Tabata, Lucas Fernando [UNESP]; Gennari-Filho, Humberto [UNESP] (My University, 2008)
Purpose: The aim of this study was to compare 2 different methods of assessment of implants at different inclinations (90 degrees and 65 degrees)-with a profilometer and AutoCAD software. Materials and Methods: Impressions (n = 5) of a metal matrix containing 2 implants. 1 at 90 degrees to the surface and 1 at 65 degrees to the surface, were obtained with square impression copings joined together with dental floss splinting covered with autopolymerizing acrylic resin, an open custom tray, and vinyl polysiloxane impression material. Measurement of the angles (in degrees) of the implant analogs were assessed by the same blinded operator with a profilometer and through analysis of digitized images by AutoCAD software. For each implant analog, 3 readings were performed with each method. The results were subjected to a nonparametric Kruskal-Wallis test, with P ≤ .05 considered significant. Results: For implants perpendicular to the horizontal surface of the specimen (90 degrees), there were no significant differences between the mean measurements obtained with the profilometer (90.04 degrees) and AutoCAD (89.95 degrees; P = .9142). In the analyses of the angled implants at 65 degrees in relation to the horizontal surface of the specimen, significant differences were observed (P = .0472) between the mean readings with the profilometer (65.73 degrees) and AutoCAD (66.25 degrees). Conclusions: The degrees of accuracy of implant angulation recording vary among the techniques available and may vary depending on the angle of the implant. Further investigation is needed to determine the best test conditions and the best measuring technique for determination of the angle of the implant in vitro.
Keywords: Dental implants; Prostheses; Software validation; Systems analysis